2020
DOI: 10.1002/ejic.202000202
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Intercalation Strategy for the Encapsulation of a CO‐Releasing Organometallic Molecule in a Layered Double Hydroxide

Abstract: The photoactivatable CO-releasing molecule (photo-CORM) [Mo(CO) 3 (CNCH 2 COOH) 3 ] (ALF795) has been incorporated into a Zn,Al layered double hydroxide (LDH) host by a coprecipitation synthesis strategy. Powder X-ray diffraction (PXRD) of the resultant material Zn,Al-ALF795 showed that the ALF795 guest molecules assembled into a monolayer to give a basal spacing of 16.0 Å. FTIR and 13 C{ 1 H} CP MAS NMR spectroscopy confirmed that the molecular structure of the tricarbonyl complex was retained upon intercalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Up to date, various guest species, including inorganic and organic molecules, have been successfully intercalated into LDHs, which usually requires a separate interlayer anion exchange process. Calhau et al incorporated a kind of photoactivatable CO-releasing molecule into the ZnAl-LDH host by a one-pot coprecipitation method, which simplified the synthesis process 251 . Doping is another effective way to improve the intrinsic activity of LDH-based materials.…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…Up to date, various guest species, including inorganic and organic molecules, have been successfully intercalated into LDHs, which usually requires a separate interlayer anion exchange process. Calhau et al incorporated a kind of photoactivatable CO-releasing molecule into the ZnAl-LDH host by a one-pot coprecipitation method, which simplified the synthesis process 251 . Doping is another effective way to improve the intrinsic activity of LDH-based materials.…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…In 2020, Isabel S. Goncalves and Martyn Pillinger et al utilized a one-pot method to introduce ALF795 into zinc, aluminium layered double hydroxide (LDH), resulting in the creation of a light-triggered CO releasing material that retains the photoactive properties of the original CORM while preventing premature dissociation and maintaining potential toxic residual segments within the LDH matrix. After incubation at 37 °C for 5 h and ultraviolet radiation, only 2% of molybdenum was leachable, indicating excellent stability and biocompatibility [ 123 ]. This observation highlights the remarkable capability of LDH hosts in effectively preserving both intact CORMs and decarbonylated fragments.…”
Section: Cornms Based On Inorganic Nanomaterialsmentioning
confidence: 99%
“…For the CORM@SiO 2 system, the inaccessibility of some surface azido groups limited the degree of functionalization to 22% . To achieve higher CO payloads, porous or layered materials have been studied as nanocarriers. The first report of this approach described the adsorption of CO on coordinatively unsaturated sites (CUS) in MIL-88B-Fe metal–organic frameworks (MOFs) . When the CO-loaded MOFs were immersed in phosphate buffered saline (PBS), framework degradation led to decarbonylation.…”
Section: Introductionmentioning
confidence: 99%
“…The amounts of CO released indicated that only 9–17% of CUS in the parent MOFs were occupied by CO, which may have been due to the access of CO molecules to internal CUS being kinetically hindered by the relatively narrow micropores of MIL-88B. Other research in this area involved the noncovalent encapsulation of manganese, rhenium, and molybdenum tricarbonyl complexes in mesoporous materials, layered materials, and MOFs. Mixed results were obtained with respect to the capacity of the carriers to retain the CORMs and/or iCORMs while incubated in biological buffer solutions. For example, an Al-doped mesoporous silica (Al-MCM-41) retained ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation